Influence of Ammonia on the Corrosion Behavior of a Zr–Sn–Nb Alloy in High Temperature Water - Chen, Zirui; Zhao, Yongfu; Tang, Min; Yin, Zhaohui; Gong, Bin; Wu, Zongpei (Frontiers in Materials, 2022)
Corrosion behaviors, microstructures of oxide films and hydrogen absorptions of a Chinese domestic Zr alloy in 6.7×10-3 mol/L ammonia solution and 2.9×10-4 mol/L LiOH+9.3×10-2 mol/L H3BO3 solution at 360℃, 18.6MPa were studied. Weight gains, oxide films thicknesses and hydrogen absorptions showed that the corrosion rate in the ammonia solution is a little higher than that in boron-lithium solution. There is no significant difference in microstructure and crystalline structure between the oxides films formed in the two types of solutions. The element distributions along the depth direction of the oxides films showed the existence of nitrogen in the oxide film formed in ammonia solution. Moreover, nitrogen was found segregate at local areas in a range of about 2μm from oxide/metal interface. The corrosion behavior of the Chinese domestic Zr alloy in 360℃ aqueous solution shows no difference with other Zr alloys.